Chronic obstructive pulmonary disease exacerbation and inhaler device handling: real-life assessment of 2935 patients. Issue 2 (16th February 2017) - Molimard, Mathieu; Raherison, Chantal; Lignot, Severine; Balestra, Aurelie; Lamarque, Stephanie; Chartier, Anais; Droz-Perroteau, Cecile; Lassalle, Regis; Moore, Nicholas; Girodet, Pierre-Olivier
Acute exacerbations of chronic obstructive pulmonary disease (COPD) can be prevented by inhaled treatment. Errors in inhaler handling, not taken into account in clinical trials, could impact drug delivery and minimise treatment benefit. We aimed to assess real-life inhaler device handling in COPD patients and its association with COPD exacerbations. To this end, 212 general practitioners and 50 pulmonologists assessed the handling of 3393 devices used for continuous treatment of COPD in 2935 patients. Handling errors were observed in over 50% of handlings, regardless of the device used. Critical errors compromising drug delivery were respectively made in 15.4%, 21.2%, 29.3%, 43.8%, 46.9% and 32.1% of inhalation assessment tests with Breezhaler® (n=876), Diskus® (n=452), Handihaler® (n=598), pressurised metered-dose inhaler (pMDI) (n=422), Respimat® (n=625) and Turbuhaler® (n=420). The proportion of patients requiring hospitalisation or emergency room visits in the past 3 months for severe COPD exacerbation was 3.3% (95% CI 2.0–4.5) in the absence of error and 6.9% (95% CI 5.3–8.5) in the presence of critical error (OR 1.86, 95% CI 1.14–3.04, p<0.05). Handling errors of inhaler devices are underestimated in real life and are associated with an increased rate of severe COPD exacerbation. Training in inhaler use is an integral part of COPD management. Inhaler mishandling is frequent and associated with increased severe COPD exacerbation http://ow.ly/rRvU3069S0Y